Science and soccer : developing elite performers - Williams, A. M. 1965- (Routledge, 2013)
"Now in a fully revised and updated third edition, Science and Soccer is still the most comprehensive and accessible introduction to the physiology, biomechanics and psychology behind the world's most popular sport. Offering important guidance on how science translates into practice, the book examines every key facet of the sport, with a particular focus on the development of elite performers. The topics covered include: - anatomy, physiology, psychology and biomechanics; - principles of training; - nutrition; - physical and mental preparation; - playing surfaces and equipment; - decision-making and skill acquisition; - coaching and coach education; - performance analysis; - talent identification and youth development. Science and Soccer: Developing Elite Performers is a unique resource for students and academics working in sports science. It is essential reading for all professional support staff working in the game, including coaches at all levels, physiotherapists, conditioning specialists, performance analysts, club doctors and sport psychologists"--